Negative pressure assisted dressings: a game changer in wound care? - Dr.Karan K Shetty; Srinivas N.M.; Avinash Chandra Singh (Asian Pacific Journal of Health Sciences, 2018)
Background: Wounds and their management is the cardinal groundwork for a surgical practice. Wound management has been an ever evolving field. The methods we employ currently are nowhere close to the time of inception of wound management. Negative pressure–assisted wound closure has brought a significant change in the management of wounds and has also improved the overall outcome. The present study is conducted to assess the efficacy of topical negative pressure moist wound dressing as compared to conventional moist wound dressings in revamping the healing process in chronic wounds and ulcers. Methods: A prospective randomised control study consisting 100 patients for the treatment of chronic wounds. They were randomly divided into two groups i.e. topical negative pressure moist dressing group and moist saline dressing for their wound. Follow up of wound was done in all cases and wound assessed depending on wound size, wound bed score, % of granulation tissue cover on first and second week for both the wound dressings group and a comparison was made between the two. Results: The most common cause of the ulcer was secondary to diabetes ( 42%).The percentage reduction of percentage of wound in the study group ( 19.52 ± 7.67), the mean difference in wound bed score and the percentage of granulation tissue formation ( 81.0 ±8.29) in the study group( 9.60 ±2.16) between presentation and subsequent follow-ups were statistically significant. Conclusions: The topical negative pressure dressing group was better in every way when compared to the conventional wound dressing group. It was also seen it is cost effective and overall hospital stay is less. It has and probably will continue to be a major influencer in the field of wound care.